Conspecific density affects predator‐induced prey phenotypic plasticity. Issue 6 (30th June 2015) - Guariento, Rafael D.; Carneiro, Luciana S.; Esteves, Francisco A.; Jorge, Jaqueiuto S.; Caliman, Adriano
Abstract : The risk‐assessment hypothesis (R‐AH) states that prey must consider conspecific density and not simply the concentration of predation cues to evaluate actual predation risk. However, little is known about whether the R‐AH might serve to predict predator‐inducible plastic responses involving different prey phenotypes. We approached this question through an experiment in outdoor mesocosms, manipulating predation risk (with caged predators) and prey conspecific density to test the importance of R‐AH for the expression of predator‐induced morphological and behavioral phenotypes. We found behavioral (swimming activity) and morphological (tail width and tail muscle depth) responses of bullfrog tadpoles ( Lithobates catesbeianus ) to be affected by chemical predation cues. However, only the morphological phenotype responded to the predation‐risk : conspecific‐density interaction. The width of the tail and the muscle depth of tadpoles were significantly greater when individuals were exposed to predators. However, this effect was not significant in treatments with high prey density in an experimental setup that minimized intraspecific competition. We interpret the differences found among the responses of the phenotypes in terms of the effects of three factors: the potential costs related to each phenotype expression, how these phenotypes are affected by environmental conditions and the immediate response of the phenotypes to actual and perceived prey risk. Our results shed light on the fact that prey individuals use information about population density to estimate actual predation risk from chemical cues. However, different traits are differentially affected, suggesting that trade‐off mechanisms associated with the costs of the expression in terms of anti‐predator defenses may interfere with the predictions of R‐AH for multiple prey phenotypes.